Pelatihan Pembuatan Robot Line Follower untuk Meningkatkan Pengetahuan Robotika pada Siswa SMK Negeri I Kramatwatu - Siswanto*, Siswanto; Sigit, Haris Triono (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2019)
Robotics is one of the right media to introduce the field of technology to students because it can help in the development of thinking, sharpening capabilities in thinking, and the ability to form concepts. The development of robot technology is currently experiencing a rapid increase so it is important for students to gain robotics knowledge to face challenges in the era of industrial revolution 4.0. But not all schools have the facilities and human resources for learning robotics. SMK Negeri I Kramatwatu in the Serang area are currently studying robot technology but only in theory, so the results are not effective. This Community Service activity is carried out as an effort to improve the knowledge and skills of students at SMK Negeri I Kramatwatu in the form of training in making Line Follower robots, a type of mobile robot whose mission is to detect and follow a guideline that has been created in the field of trajectories. Line Follower Robot was chosen as training material because this robot is one type of automatic robot that is not too complicated in its manufacture. In this training, the participants were divided into 4 groups, each guided by one mentor. The results of community service show students' enthusiasm and desire to obtain knowledge in making Line Follower robots. This can be seen when tested on robots that have been made by 4 groups of participants, namely from 4 groups of participants 3 groups have succeeded in making a Line Follower robot that can run automatically in following the trajectory.